Pengaruh pemberian somatotropin pada saat kebuntingan terhadap pertumbuhan anak tikus - N. Kusumorini; A.S. Satyaningtijas (Hemera Zoa, 2009)
Mortality, growth and conception development after placentation are affected by capacity and placenta function which are influenced by hormonal and growth factor to succed pregnancy till birth. Growth hormone is protein or polypeptide hormone. It influences protein metabolism, increases amino acid up take, carbohydrate metabolism, gluconeogenesis, fat mobilizatin, minerals metabolism and the development of cartilage that will lead to growth. The purpose of this research is to observe the effectiveness of somatotropin on the growth of fetus. Forty pregnant rat were divided to 4 groups, they were K (not given somatotropin), A (given somatotropin 9 mg/kg BW at 12 to 20 days of pregnancy), B (given somatotropin  9 mg/kg BW at 2 to 11 days of pregnancy), C (given somatotropin  9 mg/kg BW  at 2 to 20 days of pregnancy). Parameters observed were ovulation rate, implantation rate, development/growth of uterus and placenta, size of fetus, and pups growth. The result showed that somatotropin could increase implantation succed, development of uterus and placenta that are followed by good performance of reproduction during pregnancy and also birth body weight pups.Keywords: Somatotropin, Pregnancy, Pups.